Neuroimmune interactions and kidney disease - Sho Hasegawa; Tsuyoshi Inoue; Reiko Inagi (The Korean Society of Nephrology, 2019)
The autonomic nervous system plays critical roles in maintaining homeostasis in humans, directly regulating inflammation by altering the activity of the immune system. The cholinergic anti-inflammatory pathway is a well-studied neuroimmune interaction involving the vagus nerve. CD4-positive T cells expressing β2 adrenergic receptors and macrophages expressing the alpha 7 subunit of the nicotinic acetylcholine receptor in the spleen receive neurotransmitters such as norepinephrine and acetylcholine and are key mediators of the cholinergic anti-inflammatory pathway. Recent studies have demonstrated that vagus nerve stimulation, ultrasound, and restraint stress elicit protective effects against renal ischemia-reperfusion injury. These protective effects are induced primarily via activation of the cholinergic anti-inflammatory pathway. In addition to these immunological roles, nervous systems are directly related to homeostasis of renal physiology. Whole-kidney three-dimensional visualization using the tissue clearing technique CUBIC (clear, unobstructed brain/body imaging cocktails and computational analysis) has illustrated that renal sympathetic nerves are primarily distributed around arteries in the kidneys and denervated after ischemia-reperfusion injury. In contrast, artificial renal sympathetic denervation has a protective effect against kidney disease progression in murine models. Further studies are needed to elucidate how neural networks are involved in progression of kidney disease.